Developing an Accounting Information System Based on Artificial Intelligence to Improve the Quality of Accounting Information and the Decision-Making Process: Pengembangan Sistem Informasi Akuntansi Berbasis Kecerdasan Buatan untuk Meningkatkan Kualitas Informasi Akuntansi dan Proses Pengambilan Keputusan - Fayiz Hazem Al-Obaidy (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Artificial intelligence (AI) enables systems to understand and interpret data, facilitating intelligent decision-making without human interaction. Specific Background: Traditional accounting systems are fraught with flaws that compromise the quality of accounting information and decision-making processes. Knowledge Gap: There is a need for advanced AI applications to improve the accuracy of accounting data by precisely evaluating vast amounts of data, identifying errors and corrections, and accelerating financial report creation. Aims: This quantitative study aims to enhance accounting information quality by developing an AI-based accounting information system and examining its impact on the decision-making process. Results: The research utilized questionnaires to gather opinions from accountants at Rafidain Bank, Iraq, and analyzed the data using SPSS. Findings reveal that modern AI technologies significantly enhance accounting data accuracy, with a 90% success rate in detecting and correcting errors. Additionally, AI technology accelerates financial reporting, reducing the average response time to 250 milliseconds, thereby saving time and effort in accounting processes. Novelty: This study is pioneering in its comprehensive evaluation of AI's role in improving accounting data accuracy and operational efficiency within financial institutions. Implications: The research underscores the importance of upgrading device and data processing infrastructure to maximize the performance of AI-based accounting systems. The findings suggest that integrating contemporary AI technology in accounting can streamline operations, save accountants time, and boost the overall efficiency of financial and accounting institutions. Highlight: AI improves accounting data accuracy with 90% error detection and correction. AI accelerates financial reporting, reducing response times to 250 milliseconds. Upgraded infrastructure is crucial for optimal AI system performance. Keyword: Artificial Intelligence, Accounting Information, Data Accuracy, Financial Reporting, Decision-Making